The Impact of Problem-Based Learning on Learning Outcomes Using the Effect Size Calculator for T-Test - Muslim; Ambiyar; Wakhinuddin; Usmeldi; Arif, Ahmad (Universitas Pendidikan Ganesha, 2023)
Various kinds of research that has been conducted on the effect of problem-based learning on learning outcomes have varied and sometimes conflicting outputs, so it is necessary to carry out a meta-analysis. This article presents a meta-analysis regarding the impact of problem-based learning in improving student learning outcomes. This type of research is based on the source of meta-analysis in the form of experimental or quasi-experimental and observational research with a quantitative approach. Data analysis was seen from the effect size using a calculator for t-test. The subjects in the research are studies that are collected in the form of articles related to the purpose of the research. The results of the analysis of 26 article sources, obtained an average effect size of around 0.79 in the medium category. Problem-based learning is indeed effective in improving student learning outcomes. The implication of doing meta-analysis is to be able to find out more accurately about problem-based learning approaches that are effective in improving student learning outcomes as well as useful information for policy makers in the field of education.